Clinical characterization and antimicrobial resistance of Escherichia coli in pediatric patients with urinary tract infection at a third level hospital of Quito, Ecuador - David Garrido; Santiago Garrido; Miguel Gutiérrez; Leonel Calvopiña; Amani Sunday Harrison; Michelle Fuseau; Ramiro Salazar Irigoyen (Permanyer, 2017)
Background: Urinary tract infections (UTI) are among the most common infections in pediatric patients. The main etiopathogenic agent is Escherichia coli. The purpose of this study was to determine the antimicrobial resistance pattern of E. coli in pediatric patients and to understand their main clinical and laboratory manifestations. Methods: Fifty-nine patients were included in the study and classified into two groups: hospitalization (H) and external consultation (EC). Every patient presented urine cultures with the isolation of E. coli that included an antibiogram. Clinical signs and symptoms, urinalysis, complete blood count (CBC) and serum inflammatory markers were analyzed. Results: The most common clinical manifestations were fever (H: 76.5%; EC: 88%), vomiting (H: 32.4%; EC: 32%), hyporexia (H: 20.6%; EC: 16%), abdominal pain (H: 20.6%: EC: 28%), and dysuria (H: 14.7%; EC: 32%). Ten patients (16.95%) presented UTI for extended spectrum beta-lactamase (ESBL) E. coli. Ampicillin, nalidixic acid, and trimethoprim-sulfamethoxazole showed a higher resistance rate, being ampicillin the most significant (H: 88.2%; EC: 92%). Leukocyturia, bacteriuria and urine nitrites were frequent alterations in urinalysis (H: 52.9%; EC: 92%). In ESBL E. coli patients, a positive correlation was found between leukocytes in CBC and C-reactive protein (r = 0.9, p < 0.01). Diarrhea and foul-smelling urine were associated with E. coli resistance. Conclusions: The presence of leukocytes, bacteria, nitrites and the Gram stain are the most common indicators. Nitrofurantoin and phosphomycin are good therapeutic options. However, an antibiogram must be conducted to determine the best therapeutic agent.